Education and personal outlook beginning of XXI century - Бєглий, Олександр Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Article justifies the need for introduction in educational process of a new intro-ductory course "Оutlook identity of the third millennium" as a civilizational problem overdue beginning of XXI century.